A Cross-Sectional Study on Patient Safety Attitudes and Their Determinants Among Medical Staff in Malaysian Public Specialist Hospitals - Sayed Abdul Hamid, Sharifah Balqis; Ismail, Aniza; Sulong, Saperi (UI Scholars Hub, 2025)
Introduction: This study aimed to assess the baseline level and mean scores of patient safety attitude domains among doctors and nurses in Malaysian public hospitals and to identify determinants associated with these attitudes across six domains: teamwork, safety climate, working conditions, job satisfaction, stress recognition, and perception of management. Methods: A cross-sectional study was conducted using the Safety Attitudes Questionnaire (SAQ) among 142 doctors and 231 nurses from three public tertiary hospitals. Participants were selected through proportionate stratified random sampling. Data were analyzed using descriptive, bivariate, and multivariate methods. Results: The study achieved an 81% response rate. Among the six domains, job satisfaction scored the highest (mean = 73.78 ± 20.54), while perception of management scored the lowest (mean = 58.98 ± 16.28). Significant determinants of more positive patient safety attitudes included position and attendance at patient safety training (teamwork); training attendance (safety climate); education level, position, and training (job satisfaction); age and work area (perception of management); and age and training attendance (working conditions). Conclusion: Attendance at patient safety training was consistently linked to more positive attitudes, underscoring the value of continuous education in strengthening safety culture. Systematic interventions targeting education, communication, reporting, and work environment are essential to achieve the Malaysian Patient Safety Goals.